Lean Manufacturing: from the Craft Production to the Global Emergence - Elrhanimi, Samah; El abbadi, Laila; Abouabdellah, Abdellah (International Journal of Engineering and Technology, 2018)
Thanks to its promises of the industrial corporate performances improvement, Lean manufacturing is able to draw a lot of attention these last years. Since 1980, Lean manufacturing began to invade the world, thanks to the IMVP â€œInternational Motor Vehicle Programâ€ led by MIT â€œMassachusetts Institute of Technologyâ€. From this time, the concept of Lean manufacturing is a subject of study so much for the researchers who try to understand and to encircle it, that for the practitioners who want to pull the maximum from it. It is in this context that our work aims at a proposal of the Lean manufacturing definition based on the different definitions given by different authors, an analyze of the exact origin of the Lean manufacturing via a literature review and defining the six big steps that Lean manufacturing knew since its establishment until now. Â Â